Unraveling Moreton Bay reef history: An urban high-latitude setting for coral development - Hammerman, Nicholas M.; Roff, George; Lybolt, Tracy; Eyal, Gal; Pandolfi, John M. (Frontiers in Ecology and Evolution, 2022)
High-latitude habitats have become increasingly recognized as a potential climate refuge for coral communities, supporting both tropical and sub-tropical corals. Despite the increasing interest in the ecology of high-latitude corals, our current knowledge of their temporal dynamics is limited, especially within urbanized settings. Here we examined the entire history of a high-latitude coral reef ecosystem in an urbanized setting. We surveyed Holocene fossil and modern coral communities along a water quality gradient in Moreton Bay, southeast Queensland, Australia, representing near-river (Wellington Point), intermediate (Peel Island) and near-oceanic (Myora Reef) environmental conditions. Reef accretion occurred during three discrete episodes from 7,400 to 5,800, 4,900 to 3,000, and 2,100 to 300 years BP, each separated by roughly 1,000-year hiatuses, where conditions were probably not favorable enough for reef accretion to occur. Episodic reef initiation and termination suggests strong environmental controls over reef development. Eastern Australian Holocene reef growth and cessation has been linked previously to sea level fluctuations and climatic regimes (e.g., ENSO). Within each reef building episode, there were few changes in coral assemblages over time. The fast growing and branching Acropora had a relative abundance greater than 90% in ten of the 13 sediment cores and all the submerged terrace excavations. However, substantial modification of adjacent coastal catchments from European colonization in the mid 1800’s resulted in increased sediment and nutrient discharge into the bay. This perturbation coincided with a greater abundance of stress-tolerant coral species (e.g., Dipsastrea, Goniastrea and Goniopora) and the near extirpation of Acropora in the modern coral communities of near-river and intermediate sites due to poor water quality. In contrast, the modern coral assemblage at the near-oceanic site (Myora Reef) continues to be dominated by Acropora, likely due to the consistent oceanic input, resulting in lower sediment loading and higher water quality. In order for conditions for reef growth to improve, especially within the near-river portions of the bay, further sediment and nutrient runoff from anthropogenic land-use changes need to be mitigated. Given the historical abundance of Acropora, we recommend this genus be used as an indicator of natural resource management success in the bay.